Alcohol abuse and the risk of pancreatic cancer. Issue 2 (1st August 2002) - Ye, W; Lagergren, J; Weiderpass, E; Nyrén, O; Adami, H-O; Ekbom, A
Abstract : Background: Although most epidemiological studies do not support a role for alcohol in the aetiology of pancreatic cancer, an increased risk among heavy drinkers cannot be excluded. Methods: In a retrospective cohort based on the Swedish Inpatient Register, we analysed the risk of pancreatic cancer among patients admitted to hospital for alcoholism (n=178 688), alcoholic chronic pancreatitis (n=3500), non-alcoholic chronic pancreatitis (n=4952), alcoholic liver cirrhosis (n=13 553), or non-alcoholic liver cirrhosis (n=7057) from 1965 to 1994. Follow up through to 1995 was accomplished by linkage to nationwide registers. Standardised incidence ratios (SIRs) express the relative risks by taking the general Swedish population as reference. To minimise the possible influence of selection bias, we excluded the first year observations. Results: Alcoholics had only a modest 40% excess risk of pancreatic cancer (SIR 1.4, 95% confidence interval (CI) 1.2–1.5). Overrepresented smokers among alcoholics might confound a true SIR of unity among alcoholics to approximately 1.4. SIR among alcoholic chronic pancreatitis patients (2.2, 95% CI 0.9–4.5) was considerably lower than that among non-alcoholic chronic pancreatitis patients (8.7, 95% CI 6.8–10.9), and decreased with increasing duration of follow up in both groups, indicating that most of the excess might be explained by reversed causation from undiagnosed cancers. Among patients with alcoholic liver cirrhosis, the increased risk of pancreatic cancer was also moderate (SIR 1.9, 95% CI 1.3–2.8) while no significant excess risk was found among non-alcoholic liver cirrhosis patients (SIR 1.2, 95% CI 0.6–2.2). Conclusions: The excess risk for pancreatic cancer among alcoholics is small and could conceivably be attributed to confounding by smoking.